Chemically and morphologically distinct grain boundaries in Ge-doped Cu2ZnSnSe4 solar cells revealed with STEM-EELS. (15th May 2017) - Thersleff, Thomas; Giraldo, Sergio; Neuschitzer, Markus; Pistor, Paul; Saucedo, Edgardo; Leifer, Klaus
Abstract: Critical to the future development of Cu2 ZnSnSe4 (CZTSe) materials is a comprehensive understanding of the underlying nanoscale mechanisms responsible for reduced performance. Investigating these mechanisms is challenging since they arise on the nanoscale, yet manifest themselves over macroscopic regions. Here, we present an analytical study combining Scanning Transmission Electron Microscopy (STEM), sample preparation, and hyperspectral Electron Energy Loss Spectroscopy (EELS) mapping techniques to meet this challenge. We apply our method to a Ge-doped CZTSe sample with a measured efficiency of 10.1%, revealing that its microstructure is dominated by two distinct types of grain boundaries. The first type appears in the upper half of the absorber separating large grains. These are Cu-enriched, Se-poor, and have varying amounts of O. The second type of grain boundary is largely parallel to the substrate and appears predominately in the lower half of the absorber where the Cu/Zn ratio of the kesterite material is slightly lower. These grain boundaries contain voids and Sn oxide nanoparticles, exhibit high concentrations of Na, Cd, and S, and Cu assumes a higher valence state. We conclude with a discussion on the nature of and possible technological implications of these grain boundaries in this system. Graphical abstract: Highlights: Advanced analytical STEM investigation of a Ge-doped CZTSe film with 10.1% efficiency performed Two types of grain boundaries identified Chemical segregation of absorber layer into two stoichiometrically-distinct layers observed Lower grain boundaries are poorly connected, propagate parallel to the back contact, and have SnO nanoinclusions Well-connected, straight grain boundaries are Cu-rich and appear in the upper half of the film